The economic rise of China: An integrated analysis of China's growth drivers - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2024)
The economic rise of China has changed the global economy. The authors explore China's transformation from a low-cost manufacturing hub to an increasingly innovation- and service-driven economy. Major growth drivers for the period 2010-2025 are analysed, including the paradigms of "Made in China" and the "Dual Circulation Strategy". The export intensity of China's economy is declining overall, with a tendency towards greater regional diversification and a gradual decoupling from North America and the European Union. At the same time, trade and investment activities are increasingly geared to the Belt and Road Initiative. Furthermore, labour and energy cost advantages for manufacturing operations in China are likely to diminish in the coming years, calling into question China's attractiveness as a global manufacturing hub. In this regard, the further development of regional and industrial clusters is pivotal for China to enhance its global competitiveness and remain an attractive destination for foreign direct investment (FDI) in the medium term. On the other hand, high productivity in science and technology and rich deposits of critical minerals put China in a favourable position in advanced industries. Important challenges include the still wide development gap between rural and urban areas, the structural mismatch in the labour market, with persistently high youth unemployment, and the race to achieve carbon neutrality by 2060.
Keywords: F01; F14; O1; O53; 330